Pelatihan Dan Pengenalan Teknologi Bagi Masyarakat Akademis SMK Wilayah Semarang - Eddy Nurraharjo; Herny Februariyanti; Muji Sukur (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Mastering automation technology is crucial in the era of Industry 4.0, particularly for the academic community in Vocational High Schools (SMK), which plays a key role in producing skilled workers. However, a lack of understanding and access to this technology among teachers and students in SMKs across Semarang poses a significant challenge in meeting the growing demands of the industrial sector. This community service initiative aims to provide training and introduce automation technology to the academic community of SMKs in the Semarang region. The training is designed to enhance the competencies of teachers and students in operating and applying automation technology through practical and interactive approaches. The expected outcome of this initiative is an improved understanding and skill set among participants in utilizing automation technology, thereby boosting the competitiveness of SMK graduates in the job market. This program is also anticipated to serve as a model for integrating automation technology into the curriculum of other SMKs in Indonesia.